THE EFFECT OF CHINA'S TAX REFORMATION ON ENTERPRISES - Feng Yi; Agus Suroso (Faculty of Economics and Business Universitas Jenderal Soedirman, 2013)
The Central People's Government Administration Council issued and announced “The decision on the harmonization of national tax administration